(untitled) (Economics and region, 2018)
The article considers the economic essence of current liabilities, discloses their role and place in the accounting and financial reporting of the enterprise. The classification of current liabilities is investigated and summarized. The normative base for determining the term of commitment in normative legal documents is analyzed. In the article an algorithm for carrying out the analysis of current liabilities at the enterprises of Ukraine in order to reduce bankruptcy is constructed. The dynamics of current liabilities for the period 2015-2016 is analyzed, and the largest share of current liabilities in the branches of the economy is determined. Also analyzed is the share of accounts payable at enterprises. The share of short-term loans of banks in the sectors of the economy of Ukraine is determined. The analysis of the relevant indicators is made on the basis of the state site of statistics of Ukraine. It was investigated that obligations arise as a consequence of past events, namely after receipt of goods, works, services, advances, as well as the calculation of wages, taxes, fees, etc. Liabilities are considered current if the unplanned period of their repayment does not exceed 12 months from the balance sheet date. According to the results of the study, it was concluded that current liabilities are used in analyzing the financial condition of an enterprise to determine its solvency and liquidity, and to a large extent affect the financial position of enterprises.